Towards a post-Covid global financial system : lessons in social responsibility from Islamic finance - Hassan, M. Kabir; Muneeza, Aishath; Sarea, Adel M. (Emerald Publishing Limited, 2022)
The impact of COVID-19 has exposed major cracks in the global financial system and has severely undermined global financial stability. Never have the shortcomings of universal financialization - the dominant principle of the global financial system for the past thirty-odd years - been more obvious or more painful. Islamic finance provides ways forward: based on commercial and social modes of risk-sharing and financing, it offers radical structural solutions to the health, human and financial crises faced in this unprecedented time. In Towards a Post-Covid Global Financial System: Lessons in Social Responsibility from Islamic Finance, an international team of experts explore how COVID-19 has affected the most vulnerable parts of the global economy; how it has been met by Islamic banking and finance specifically; and how the principles of Islamic social finance could be used to have a fairer, more resilient Islamic finance system for all.